PERKEMBANGAN ANAK USIA PRASEKOLAH YANG MENGGUNAKAN SMARTPHONE DI RA (RAUDHATUL ATHFAL) AISIYAH DESA BANDARAN PAMEKASAN - RAHMAN, HILMAH NOVIANDRY (Jurnal Sains dan Teknologi Kesehatan, 2024)
Introduction: Preschoolers develop in various aspects. This preschool period is the right time to develop various potentials and abilities, including fine and gross motor skills, speech language, and social independence. Preschool children can experience developmental disorders caused by several factors, one of which is smartphones. The purpose of this study was to determine the development of preschool age children using smartphones in RA Aisiyah Bandaran Pamekasan Village in 2022. Methods: The design used in this study was descriptive with the observation method. The population in this study were 39 people of pre-school age who used smartphones in RA Aisiyah Bandaran Pamekasan Village. Sampling technique non-probability total sampling with a sample of 39 people. The instrument used was a developmental pre-screening questionnaire (KPSP), which was then analyzed descriptively (percentage), the results were presented in tabular and narrative form. Results : The research shows that the development of preschool-aged children who use smartphones is almost entirely in accordance with as many as 32 respondents (82%). Conclusion : It is hoped that the school will develop stimulation to help children develop more optimally especially children who use smartphones and monitor their growth and development every 2 weeks. Meanwhile, mothers should limit the use of smartphones because they can improve child development. Keywords : preschool age children, development, smartphone